Elucidating the photocatalytic degradation pathway of acetaldehyde: An FTIR in situ study under atmospheric conditions - Hauchecorne, Birger; Terrens, Dieter; Verbruggen, Sammy; Martens, Johan A.; Van Langenhove, Herman; Demeestere, Kristof; Lenaerts, Silvia (Applied catalysis. B, Environmental, 2011)
[Display omitted] • FTIR in situ reactor used for real time study of photocatalytic acetaldehyde removal. • Formation of crotonaldehyde and 3-hydroxybutanal upon adsorption of acetaldehyde on TiO2. • Acetic acid, formic acid, formaldehyde and their respective conjugated bases are found as reaction intermediates. In this paper, new insights of the photocatalytic oxidation pathway of acetaldehyde are obtained by means of an in-house constructed FTIR in situ reactor. It is shown that there are generally three different intermediates present: acetic acid, formic acid and formaldehyde. By means of FTIR in situ spectroscopy, this study revealed that these intermediates are bound on the TiO2 surface in different ways, resulting in the presence of more intermediate species, such as molecularly adsorbed acetic acid, bidentate acetate, molecularly adsorbed formic acid, monodentate formate, bidentate formate, formaldehyde and dioxymethylene. Furthermore, spectroscopic evidence is obtained concerning the formation of 3-hydroxybutanal and crotonaldehyde upon adsorption of acetaldehyde on TiO2 prior to UV illumination. The presented results thus give new insights in the photocatalytic oxidation pathway of acetaldehyde.